Análise dos constituintes fixos e voláteis de fungos endofíticos dos gêneros Penicillium e Xylaria e de suas plantas hospedeiras - Santos Filho, Florisvaldo Clementino (Universidade Federal de São Carlos, 2010)
Was conducted the study of chemical constituents volatiles and fixed of endophytes fungi. For this, we used the Penicillium griseoroseum, Penicillium brasilianum, Xylaria (NICL3) and different species of the genus Trichoderma, was also carried out a study of host plants, such as Cupressus lusitanica and Melia azedarach. Through analysis by GC-MS and methodologies for calculations of retention indices were identified monoterpenes, sesquiterpenes and diterpenes in the oils of plant and fungus. Compounds similar to essential oils of plants and associated microorganisms led to believe in the existence of biochemical interactions. Transesterification acid reactions was used for extraction of lipid compounds that were identified, characterized and quantified by techniques GC-MS, ¹H NMR and GC-FID. Profiles of methyl esters of fatty acids were found varied according to the species used, leading to mounting a chemo-taxonomic classification. Data quantification according to EN 14 103 showed that two endophytic fungi can be considered a promising source of biofuels. Antifungal assays of essential oil of Cupressus lusitanica were performed against endophytes be showing the importance of volatile compounds in the plant-endophytic microorganism.
Analysis of constituents fixed and volatile of endophytic fungi of the genus Penicillium and Xylaria and their host plants
Keywords: Fungos endofíticos; Biodiesel; Espectrometria de massas; Compostos orgânicos voláteis; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA